Analysis Application of Integrated Variable Frequency Drive With Radar Sensor for Silo Optimization to Reduce Electricity Consumption Ratio - Khusnul Maulana Ibrahim; Hasanuddin Hasanuddin; Aris Sumarwanto (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
PT ISM Tbk Bogasari Flour Mills Surabaya is a company that processes wheat into flour and by-products. There is an achievement of the Key Result Area (KRA) work target that has not been achieved, namely the problem of the ratio of electricity consumption. From the work target set at 18 kwh/ton, the achievement of the electricity ratio is still 19.09 kwh/ton. From October-December 2020 there was a waste of Rp. 51,166,851. The purpose of this research is to reduce the ratio of electricity consumption to 18 kWh/ton. The settlement method used is a quality control circle with a method of 8 steps and 7 tools. The improvement implemented is the application of an integrated variable frequency drive with a radar sensor to determine the product contents in the silo which is controlled via PLC. The results of the target evaluation show a decrease in the ratio of electricity consumption from 19.09 kwh/ton to 17.19 kwh/ton with a cost savings of Rp. 418,245,746/year. PT ISM Tbk Bogasari Flour Mills Surabaya merupakan perusahaan yang mengolah gandum menjadi tepung terigu serta produk sampingan. Terdapat pencapaian target kerja Key Result Area (KRA) yang tidak tercapai yaitu masalah rasio konsumsi listrik. Dari target kerja yang ditetapkan sebesar 18 kwh/ton, pencapaian rasio listrik masih sebesar 19,09 kwh/ton. Selama Oktober-Desember 2020 terjadi pemborosan sebesar Rp 51.166.851. Tujuan dari penelitian ini adalah menurunkan rasio konsumsi listrik hingga 18 kwh/ton. Metode penyelesaian yang digunakan yaitu quality control circle dengan metode 8 langkah dan 7 tools. Improvement yang diimplementasikan adalah penerapan variable frequency drive terintegrasi sensor radar untuk mengetahui isi product di dalam silo yang dikontrol melalui PLC. Hasil evaluasi target menunjukkan penurunan rasio konsumsi listrik dari 19,09 kwh/ton menjadi 17,19 kwh/ton dengan penghematan biaya sebesar Rp. 418.245.746/tahun.